UPCYCLING OF TECHNOGENIC MINERAL WASTE – CHALLENGES AND SOLUTIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Industrial mineral waste accounts for a significant proportion of all global waste. In the European Union it is more than 71% (2,5 Gt ) of the total amount of non-hazardous waste - construction and demolition waste, ash and slag, tailings residues, unconditioned waste rocks, etc. In Latvia, the share of this waste is about 20%. Due to the fact that they are inert, non-biodegradable materials and cannot be used for energy production and cannot be reduced by incineration, their stocks are increasing every year. Their utilization volumes are low and focused mainly on use as backfill when carrying out various earthworks. At the same time, mineral waste, both in terms of composition and structure, physical and chemical properties, is a serious mineral resource, the processing of which can result in high-quality useful products, thus implementing the waste upcycling principle - the newly acquired product has higher added value than the original. The paper evaluates the physical and technical possibilities and perspectives for the production of eco-innovative materials from mineral waste - geopolymers, glass ceramics, porous ceramics and mineral-organic composite materials.